Correction to: Exploring the dynamics of HIV and CD4+ T-cells with non-integer derivatives involving nonsingular and nonlocal kernel (Scientific Reports, (2024), 14, 1, (24506), 10.1038/s41598-024-73580-9) - Shutaywi M.; Shah Z.; Vrinceanu N.; Jan R.; Deebani W. (Nature Research, 2025)
Correction to: Scientific Reportshttps://doi.org/10.1038/s41598-024-73580-9, published online 18 October 2024 The original version of this Article contained an error in the Funding section. ?Project financed by Lucian Blaga University of Sibiu through research grant LBUS-IRG-2023-09.? now reads: ?Project financed by Lucian Blaga University of Sibiu (Knowledge Transfer Center) & Hasso Plattner Foundation research grants LBUS-HPI-ERG-2023-05? The original Article has been corrected. ? The Author(s) 2024.